Development of A Base Learning Project Model With Online Media In An Effort to Increase Learning Activities During the COVID-19 Pandemic - M Martiano; H Maulana (International Journal of Basic and Applied Science, 2021)
Decrease in learning outcomes in operating systems courses. The decline in learning outcomes is caused by the current corona virus pandemic. Which causes face-to-face lectures to be online. Researchers use project base learning to improve learning outcomes. The application consists of 2 cycles, namely Diclus 1 which is 80.12% with the number who did not pass, namely 16 students, researcher evaluating the learning process so that in cycle 2 it increased by 83.73%. With the student’s who did not pass. It can be concluded that the base learning method can be used to improve learning outcomes during the COVID-19 pandemic.